2006
DOI: 10.1002/chem.200501564
|View full text |Cite
|
Sign up to set email alerts
|

Towards Photocontrol over the Helix–Coil Transition in Foldamers: Synthesis and Photoresponsive Behavior of Azobenzene‐Core Amphiphilic Oligo(meta‐phenylene ethynylene)s

Abstract: Introduction of photochromic azobenzene units into amphiphilic oligo(meta-phenylene ethynylene)s allowed photocontrol over the helix-coil transition in this important class of foldamers. Two design principles were followed in efforts to accommodate cis- and trans-azobenzene moieties within the helical structure to selectively turn the helical state on and off, respectively. Several oligomer series with varying connectivities to the central azobenzene chromophore were synthesized and these photochromic oligomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(50 citation statements)
references
References 38 publications
4
45
0
1
Order By: Relevance
“…as copolymer 12 is amphiphilic in nature, the driving force for such folding behavior could be the solvophobicity of the non-polar aromatic backbone in polar environment, resulting in an intramolecular segregation, analogous to nanophase separation usually encountered in amphiphilic block-copolymers. [68] 1 H-nMr, UV-vis and fluorescence spectroscopy, and aFM microscopic results corroborate the assumption that the folding was induced most probably by intramolecular π-π stacking between non-adjacent moieties in the backbone and their solvophobic interactions and that, the helical geometry was encoded in the backbone topology as well as in its constitutive parts.…”
Section: (A)]supporting
confidence: 76%
“…as copolymer 12 is amphiphilic in nature, the driving force for such folding behavior could be the solvophobicity of the non-polar aromatic backbone in polar environment, resulting in an intramolecular segregation, analogous to nanophase separation usually encountered in amphiphilic block-copolymers. [68] 1 H-nMr, UV-vis and fluorescence spectroscopy, and aFM microscopic results corroborate the assumption that the folding was induced most probably by intramolecular π-π stacking between non-adjacent moieties in the backbone and their solvophobic interactions and that, the helical geometry was encoded in the backbone topology as well as in its constitutive parts.…”
Section: (A)]supporting
confidence: 76%
“…Hecht et al reported the photoswitchable foldamers 55-57 by harnessing the photoisomerizable azobenzene unit [109,110].…”
Section: Photo-responsive Aefsmentioning
confidence: 98%
“…Hecht et al reported the synthesis of azobenzene-core amphiphilic oligo(meta-phenylene ethynylene)s. 32 After bromination of methyl 3-nitrobenzoate (39), treatment of 40 with zinc under basic conditions yielded the desired azobenzene bis-acid 41 in 63% yield (two steps) (Scheme 16).…”
Section: Reduction Reactions Of Aromatic Compounds Having Nitro Groupsmentioning
confidence: 99%